Sintesis Katalis Platina Didukung Vulcan XC 72 - Reduced Graphene Oxide Dalam Aplikasi PEMFC Dan Karakterisasi Elektrokimia Dengan Cyclic Voltametry - Wismaya, I Made Edwin; Joni, I Made; Suarda, Made; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika; Vol 14 No 1 (2025): Januari 2025 : Teknik Desain Mekanika, 2025)
Abstractt Fuel cells are a green energy device that is environmentally friendly, high quality, and has potential in various portable applications. The type of fuel cell commonly used in portable applications is a proton exchange membrane fuel cell (PEMFC). PEMFC uses hydrogen fuel which in the electrochemical process produces electricity, water and heat. This research is focused on improving the performance of PEMFC with a platinum catalyst supported by Vulcan XC 72 – reduced graphene oxide (Pt/VC-rGO). The methods used are the modified Hummer method and the impregnation method. The masses of VC and rGO were varied into 3 types, the first (0.1 gr Pt : 0.3 gr VC : 0.1 gr rGO), the second (0.1 gr Pt : 0.2 gr VC : 0.2 gr rGO), and the third (0.1 gr Pt : 0.1 gr VC : 0.3 g rGO). The results of the cyclic voltammetry test show that the results of the 0.1 gr Pt, 0.1 gr VC, and 0.3 gr RGO variations obtained better results than the three variations which showed a potential range of 0.6-0.9 V and a current of 0.0001 A. Keywords: fuel cell, PEMFC, Synthesis, Catalyst, Pt/VC-rGO, Reduced graphene oxide